Enterprise productivity: a three-speed Europe - Andrea Dall'Olio; Mariana Iootty; Naoto Kanehira; Federica Saliola (European Central Bank (ECB), 2014)
Between 2003 and 2008 productivity patterns diverged between the fast growing, newest members of the European Union and the slower paced, elder ones – as would be expected. However, there are also striking divergences within the latter group, with productivity in Southern Europe going into reverse. This paper analyzes which factors - whether countrylevel or firm-specific ones - contributed more to the emergence of a three-speed Europe. The analysis combines firm-level data with country-level inputs. Among the newest members of the European Union, country characteristics including the stock of inward foreign direct investment, the availability of credit, and the quality of the business environment and the skills of the workforce prove to be the most important drivers. Firm specific characteristics are shown to matter as well, notably that small firms and firms which are part of international groups realize more productivity gains than larger domestic competitors. Among the more advanced member countries, firm-level characteristics are most important, with larger firms and firms with international affiliation demonstrating faster productivity gains. Country specific factors, such as the quality of the business environment, the size of outward FDI and the skills of the workforce, do matter as well. These explanations of diverging productivity patterns suggest that European Union nations can realize significant benefits from low cost policy interventions such as improving business regulations and encouraging firms' internationalization.
Keywords: D22; H11; O47; O52; 330; doing business; European Union; firm characteristics; firm performance; foreign direct investment; global value chains; productivity; regulation